Pengaruh Parameter Fisika dan Mikrobiologi Leachet terhadap Kesehatan Lingkungan di TPA Muara Fajar Rumbai Pekanbaru - Riski Novera Yenita; Ade Pulasta Siprana (Jurnal Kesehatan Komunitas, 2015)
The general condition of â€œCity trashâ€ shows typical characteristics. The The city waste largest had a composition of the organic worth rata-rata 79,164 %, the inorganic waste was only 20,836 %. Type of research was a survey method. Location sampling was in Muara Fajar landfill Pekanbaru. Samples were taken and analyzed the level of physics and biology leachet in the laboratory, data obtain were then analyzed using descriptive, in accordance with SNI 06-2412-1991. The data research the interview, observation and laboratory. Two code samples to water lindi obtained analysis on codes sample that I and II or temperature is 250C. TSS on codes I got the sample of 70 mg/l and sample code II 190 mg/l. ph on codes samples I and II obtained a result of 8, as for the sample e.coli on codes I and II obtained the infinite.